THE EFFECT OF PROMOTION AND QUALITY OF SERVICE ON CONSUMER SATISFACTION ON GRABBIKE ONLINE TRANSPORTATION SERVICES - Mutia Arda; Muhammad Iqbal (Proceeding International Seminar of Islamic Studies, 2022)
GrabBike is a passenger transportation service which in its operational activities is directly related to consumers, customer satisfaction must be very concerned in order to maintain a good impression for consumers. The purpose of this study was to determine and analyze the effect of promotion on consumer satisfaction, to determine and analyze the effect of service quality on consumer satisfaction and to determine and analyze the effect of promotion and service quality on consumer satisfaction in the online transportation service GrabBike. The approach used in this study is an associative approach. The population in this study were UMSU students while the sample that met the criteria for sampling the observations made was 100 people using the Quota Sampling technique. The data collection technique in this study used a questionnaire technique. The data analysis technique in this study uses the Classical Assumption Test, Multiple Regression, t-test and F-test, and the Coefficient of Determination. Partially, it is known that promotions have a positive and significant impact on consumer satisfaction with GrabBike's online transportation service. Partially, it is known that service quality has a positive and significant impact on consumer satisfaction with GrabBike's online transportation service. Simultaneously, it is known that promotion and service quality together have a significant influence on consumer satisfaction with GrabBike's online transportation service..Keywords: Promotion, Service Quality and Consumer Satisfaction